Effets de différentes méthodes d`entraînement sur les paramètres lactiques - Gharbi, A.; Elabed, K.; Latiri, I.; Tabka, Z.; Zbidi, A. (Science & Sports, 2010)
The purpose of this study was to compare the differences in lactate parameters and maximal aerobic speed (MAS) adaptations to intermittent, mixed and continuous training. Methods. Thirty-six subjects were equally divided into continuous (CT) or intermittent (IT) or mixed (MT) training groups. The trained participants practiced six d/wk for six weeks. Before and after training, all participants completed an incremental exercise test to assess their MAS, and a 30-second supramaximal exercise followed by active recovery. Results. Blood lactate recovery curves from the supramaximal exercise were fitted to a biexponential ime function. Following the training period, there was a significant increase in MAS, a significant increase in lactate exchange ( 1) and removal ( 2) abilities, a significantly faster time to peak lactate (t-[La]peak), a significant decrease in lactate half time (t-1/2-[La]). The improvement in MAS and 1 were significantly higher in IT and MT-group compared to CT-group. The lactate removal ability ( 2) was significantly higher for IT than for CT and MT-group (p < 0.05). However, no significant differences were observed in peak blood lactate concentration ([La]peak) and in t-[La]peak between the three physically-trained groups. We conclude that both IT and MT were more efficient in elevating MAS. However, this two methods were equally effective on all others parameters except 2. IT was more beneficial in raising the lactate removal ( 2) ability.